The effects of flaveria trinervia and dicerocaryum seneciodes extracts on metastatic MDA-MB-231 breast cancer cells - Sebei, Tubake Theona (My University, 2025)
Medicinal plants have been used for centuries in various traditional healing practices worldwide. Research has revealed some of these plants contain bioactive compounds with potential anticancer and antimetastatic properties. Dicerocaryum senecioides and Flaveria trinervia have both been reported to have anti-inflammatory and antioxidative effects, which can contribute to inhibiting metastatic processes such as relocation of metastatic cells from a primary organ and subsequent adhesion to a secondary organ. Therefore, the study aimed to investigate potential antimetastatic effects of Dicerocaryum senecioides and Flaveria trinervia chloroform and methanol extracts on MDA-MB-231 breast cancer cells. The effect of the extracts on the viability of MDA-MB-231 and HEK–293 human embryonic kidney cells was assessed using the cell counting kit-8 kit. To determine the mode of cell death induced by the extracts, annexin-V and dead cell assay was employed. The effect of the extracts on reactive oxygen species formation and epithelial to mesenchymal transition-related morphological changes were evaluated with the Muse® Oxidative Stress Kit and light microscope, respectively. The transwell and cell adhesion assay were used to investigate the anti-migratory effects of the extracts on MDA-MB-231 cells as well as the ability of the cells to attach to a cell culture plate, respectively. The effects of the extracts on the enzymatic activity of the matrix metalloproteinases- 2 and -9 was assessed using gelatin-zymography. Additionally, western blotting was used to evaluate the effect of the extracts on the expression of vimentin. The findings revealed there was no significant effect on MDA-MB-231 and HEK-293 cell viability at extract concentrations below 200 μg/ml, and that cell death occurred through apoptosis at those concentrations. Reactive oxygen species formation and epithelial to mesenchymal transition were suppressed in the MDA-MB-231 cells treated with extracts. Moreover, the extracts suppressed cell invasion by inhibiting the activity of MMP-9 & -2, expression of vimentin as well as subsequent migration, and adhesion. The chloroform extracts of both plant showed better anti-migratory, anti-invasive and anti-adhesive potential than the methanol extract. Thus, this study highlighted Dicerocaryum senecioides and Flaveria trinervia as potential sources of compounds of intermediate polarity with anti-metastatic activity.
Thesis (M. Sc. (Biochemistry)) -- University of Limpopo, 2025
Keywords: Dicerocaryum seneciodes extracts; Flaveria trinervia; Metastatic MDA-MB-231; Breast cancer cells; Effects; Breast -- Cancer -- Treatment; Medicinal plants; Metastasis